Paper 82: High Variability Exists Between Longstanding Lateral Radiographs and Standard Lateral Knee Radiographs Evaluating Posterior Tibial Slope in Revision ACL Patients. Issue 7 (30th July 2022) - Steward, Joshua; Warth, Ryan; Haidar, Layla; Lowe, Walter; Mansour, Alfred
Objectives: Increased posterior tibial slope (PTS) has been identified as a risk factor for both short-term and long-term failure after anterior cruciate ligament (ACL) reconstruction. Correction of PTS may improve outcomes after revision ACL reconstruction. Conflicting reports demonstrate the most accurate way to measure the PTS on standard short knee radiographs versus longstanding lateral radiographs including the entire tibia. Many reports advocate short knee radiographs as adequate for the evaluation of posterior tibial slope and deciding surgical treatment. The purpose of this study was to compare posterior tibial slope measurements between standard short segment knee (SSK) and longstanding lateral knee radiographs (LSL) in a failed ACL cohort. We hypothesize that there is high variability in SSK measurements compared to LSL. Our secondary hypothesis is that our series of surgical deformity corrections for failed ACL reconstructions with increased PTS includes a significant number of biplanar deformities requiring altered technique to completely address all deformities. Methods: The medial and lateral PTS were measured on 35 consecutive patients with failed ACL reconstructions using SSK and LSL using previously published techniques. Coronal plane deformity was assessed by the tibiofemoral angle on AP long standing films. All measurements were made by two trained independent observers at two different times separated by one month for calculation of inter- and intra-observer reliability using intra-class correlation coefficients (ICCs). Measurements recorded by the observer with the higher intra-observer ICC for the SSK and LSL were used for calculation. Paired t-tests were used for direct comparison of tibial slope measurements between the SSK and LSL conditions. P-values less than 0.05 were considered statistically significant. Results: There was a statistically significant difference in average lateral plateau PTS between standard short knee lateral and longstanding lateral radiographs (11.0 degrees versus 12.2 degrees, P =0.031). More importantly, 66.6% of the absolute measurements differed by at least 3 degrees, with variability as high as 7 degrees in our series as shown in Figures 1 and 2. 20/35 patients (57.1%) also had varus or valgus deformity > 2 degrees. Twelve patients underwent posterior slope correction as part of their revision ACL reconstruction. 8/12 of those patients (66.7%) had varus/valgus deformity > 2 degrees, and 41.7% (5/12) of patients required biplanar proximal tibial osteotomy correction to adequately address their multiplanar deformity. Conclusions: Long segment radiographs more completely evaluate the complex deformities of posterior tibial slope associated with failed ACL reconstruction, with less variability than standard short knee radiographs. In our series, a high percentage of patients needed biplanar correction, and we recommend obtaining long segment anteroposterior and lateral radiographs as essential imaging in these patients.